2004
DOI: 10.1023/b:jots.0000014674.84517.46
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume and memory performance in a community‐based sample of women with posttraumatic stress disorder secondary to child abuse

Abstract: Childhood abuse is linked to posttraumatic stress disorder (PTSD), which follows abuse survivors into adulthood. This study identified the neuropsychological and neuromorphological sequelae of PTSD among prepubescently abused women. Right-handed women aged 20-40 years were placed into PTSD and abuse, abuse only, and normal control groups (n = 17 per group). Participants were screened for trauma history and psychiatric symptoms, demographically matched, and given neuropsychological tests and a magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(110 citation statements)
references
References 15 publications
5
95
0
10
Order By: Relevance
“…Since preclinical studies support the role for CA3 and CA1 hippocampal neurons in mediating eyeblink trace conditioning (Berger and Thompson, 1978;Clark and Squire, 1998;Moyer et al, 1990;Solomon et al, 1986;Weiss et al, 1996), the present data are similar to some studies demonstrating normal hippocampal-mediated neuropsychological function in PTSD (Neylan et al, 2004;Pederson et al, 2004;Vasterling et al, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…Since preclinical studies support the role for CA3 and CA1 hippocampal neurons in mediating eyeblink trace conditioning (Berger and Thompson, 1978;Clark and Squire, 1998;Moyer et al, 1990;Solomon et al, 1986;Weiss et al, 1996), the present data are similar to some studies demonstrating normal hippocampal-mediated neuropsychological function in PTSD (Neylan et al, 2004;Pederson et al, 2004;Vasterling et al, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…[22][23][24][25][26][27] However, as shown in our previous review, 10 there is also some disagreement about laterality 21,[28][29][30] and even about the presence of this reduction, 13,[31][32][33][34] in both ROI and VBM-based studies. These contrasting findings, in addition to being due to possible neurobiological abnormalities, may also be due to methodological limitations such as differences in the selection of the hippocampus by manual methods.…”
Section: Posttraumatic Stress Disorder (Ptsd)mentioning
confidence: 85%
“…Morphological brain abnormalities were evaluated in each study, and only four of them [13][14] have detected no significant differences between the patient and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Among studies that have reported signifi cant PTSD effects on hippocampal volume or declarative memory (but not both) and also tested structural-functional correlations, one reported positive fi ndings (Tischler et al, 2006 ;Yehuda et al, 2007 ; these publications report on the same sample) and two had negative fi ndings (Gurvits et al, 1996 ;Stein, Koverola, Hanna, Torchia, & McClarty, 1997 ). Two additional studies that gathered data relevant to these correlations did not report them (Bremner et al, 2003 ;Pederson et al, 2004 ).…”
Section: Symposiummentioning
confidence: 99%